Circulating fatty acids and risk of gestational diabetes mellitus: prospective analyses in China. Issue 1 (24th May 2021) - Pan, Xiong-Fei; Huang, Yichao; Li, Xinping; Wang, Yi; Ye, Yi; Chen, Huan; Marklund, Matti; Wen, Ying; Liu, Yan; Zeng, Huayan; Qi, Xiaorong; Yang, Xue; et al.
Abstract : Objective: We aimed to examine prospective associations between circulating fatty acids in early pregnancy and incident gestational diabetes mellitus (GDM) among Chinese pregnant women. Methods: Analyses were based on two prospective nested case-control studies conducted in western China (336 GDM cases and 672 matched controls) and central China (305 cases and 305 matched controls). Fasting plasma fatty acids in early pregnancy (gestational age at enrollment: 10.4 weeks(s.d., 2.0)) and 13.2 weeks (1.0), respectively) were determined by gas chromatography-mass spectrometry, and GDM was diagnosed based on the International Association of Diabetes in Pregnancy Study Groups criteria during 24–28 weeks of gestation. Multiple metabolic biomarkers (HOMA-IR (homeostatic model assessment for insulin resistance), HbA1c, c-peptide, high-sensitivity C-reactive protein, adiponectin, leptin, and blood lipids) were additionally measured among 672 non-GDM controls at enrollment. Results: Higher levels of saturated fatty acids (SFAs) 14:0 (pooled odds ratio, 1.41 for each 1-s.d. increase; 95% CI: 1.25, 1.59) and 16:0 (1.19; 1.05, 1.35) were associated with higher odds of GDM. Higher levels of n-6 polyunsaturated fatty acid (PUFA) 18:2n-6 were strongly associated with lower odds of GDM (0.69; 0.60, 0.80). In non-GDM pregnant women, higher SFAs 14:0 and 16:0 but lower n-6 PUFA 18:2n-6 were generally correlated with unfavorable metabolic profiles. Conclusions: We documented adverse associations of 14:0 and 16:0 but a protective association of 18:2n-6 with GDM among Chinese pregnant women. Our findings highlight the distinct roles of specific fatty acids in the onset of GDM.